OP0008 DEVELOPMENT AND VALIDATION OF AN ALTERNATIVE ANKYLOSING SPONDYLITIS DISEASE ACTIVITY SCORE WHEN PATIENT GLOBAL ASSESSMENT IS UNAVAILABLE. (2nd June 2020) - Ortolan, A.; Ramiro, S.; Van Gaalen, F. A.; Kvien, T. K.; Landewé, R. B. M.; Machado, P. M.; Ruyssen-Witrand, A.; Van Tubergen, A.; Bastiaenen, C.; Van der Heijde, D.
Abstract : Background: Ankylosing Spondylitis Disease Activity Score (ASDAS) is a composite index measuring disease activity in axial spondyloarthritis (axSpA). It includes questions from the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Patient Global Assessment (PGA), and inflammation biomarkers. However, ASDAS calculation is not always possible because PGA is sometimes not collected. Objectives: To develop an alternative ASDAS to be used in research settings when PGA is unavailable. Methods: Longitudinal data from 4 axSpA cohorts and 2 RCTs were combined. Observations were randomly split in a development (N=1026) and a validation cohort (N=1059). Substitutes of PGA by BASDAI total score, single or combined individual BASDAI questions, and a constant value, were considered. In the development cohort, conversion factors for each substitute were defined by Generalized Estimating Equations. Validation was performed in the validation cohort according to the OMERACT filter, taking into consideration: 1) Truth (agreement with original-ASDAS in the continuous score, by intraclass correlation coefficient -ICC- and in disease activity states, by weighted kappa) 2) Discrimination (standardized mean difference –SMD- of ASDAS scores between high/low disease activity states defined by external anchors e.g Patient Acceptable Symptom State –PASS-; agreement -kappa- in the % of patients reaching ASDAS improvement criteria according to alternative vs. original formulae) 3) Feasibility. Results: Taking all psychometric properties into account and comparing the different formulae (Table), alternative-ASDAS using BASDAI total as PGA replacement proved to be: 1) truthful (agreement with original-ASDAS: ICC=0.98, kappa=0.90); 2) discriminative: it could discriminate between high/low disease activity states (e.g. scores between PASS no/yes: SMD=1.37 versus original-ASDAS SMD=1.43) and was sensitive to change (agreement with original-ASDAS in major improvement/clinically important improvement criteria: kappa=0.93/0.88; 3) feasible (BASDAI total often available; conversion coefficient≈1). Conclusion: Alternative-ASDAS using BASDAI total score as PGA replacement is the most truthful, discriminative and feasible instrument. This index enables ASDAS calculation in existing cohorts without PGA. Disclosure of Interests: Augusta Ortolan: None declared, Sofia Ramiro: None declared, Floris A. van Gaalen: None declared, Tore K. Kvien Grant/research support from: Received grants from Abbvie, Hospira/Pfizer, MSD and Roche (not relevant for this abstract)., Consultant of: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Paid instructor for: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Speakers bureau: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Robert B.M. Landewé Consultant of: AbbVie; AstraZeneca; Bristol-Myers Squibb; Eli Lilly & Co.; Galapagos NV; Novartis; Pfizer; UCB Pharma, Pedro M Machado Consultant of: PMM: Abbvie, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Roche and UCB, Speakers bureau: PMM: Abbvie, BMS, Lilly, MSD, Novartis, Pfizer, Roche and UCB, Adeline Ruyssen-Witrand Grant/research support from: Abbvie, Pfizer, Consultant of: Abbvie, BMS, Lilly, Mylan, Novartis, Pfizer, Sandoz, Sanofi-Genzyme, Astrid van Tubergen Consultant of: Novartis, Caroline Bastiaenen: None declared, Désirée van der Heijde Consultant of: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Cyxone, Daiichi, Eisai, Eli-Lilly, Galapagos, Gilead Sciences, Inc., Glaxo-Smith-Kline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, UCB Pharma; Director of Imaging Rheumatology BV